1981
DOI: 10.1111/j.1365-2621.1981.tb04915.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Moraxella‐Acinetobacter Cells by Sodium Phosphates and Sodium Chloride

Abstract: The effect of sodium phosphates with and without NaCl, on the ability of unstressed and heat-stressed Moraxella-Acinetobacter (M-A) isolate number 7 cells to form colonies in plate count agar (PCA) was determined. The effectiveness, in order of decreasing ability, of phosphates to inhibit colony formation of unstressed M-A cells was as follows: sodium tripolyphosphate (NasP,Oro; STPP), sodium pyrophosphate (Na4P207; SPP), and sodium orthophosphate (NajP04; SP). Filter sterilized STPP was more inhibitory than w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1985
1985
2004
2004

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Investigators have speculated that TSP works by removing a thin layer of fat and bacteria from the surface of poultry skin (20). Many hypotheses have been made for the antibacterial mechanisms of phosphates including chelation of structurally essential metal ions in the cell walls (25,26), chelation of metal ions in the cytochrom system (27,28), repression of enzyme synthesis and inhibition of enzyme activity (29) and changes in the water activity of the media (30). Our aim was to investigate the possibility of extending the shelf-life of chicken carcasses using sodium tripolyphosphate.…”
Section: Introductionmentioning
confidence: 99%
“…Investigators have speculated that TSP works by removing a thin layer of fat and bacteria from the surface of poultry skin (20). Many hypotheses have been made for the antibacterial mechanisms of phosphates including chelation of structurally essential metal ions in the cell walls (25,26), chelation of metal ions in the cytochrom system (27,28), repression of enzyme synthesis and inhibition of enzyme activity (29) and changes in the water activity of the media (30). Our aim was to investigate the possibility of extending the shelf-life of chicken carcasses using sodium tripolyphosphate.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the effect of polyphosphates on A. hydrophila was not due to the alteration in pH. Firstenberg-Eden et al (1981) reported increased inhibitory activity of sodium phosphates against Moruxella-Acinetobacter when combined with sodium chloride. Elliott et al (1964) reported that a polyphosphate mixture was effective against pseudomonads isolated from poultry meat.…”
Section: Resultsmentioning
confidence: 96%
“…of Animal Sciences and Department of Food Science &Human Nutrition, Colorado State Univ., Fort Collins, CO 80523. -Eden et al, 1981;Nelson et al, 1983;Wagner and Busta, 1983;Tompkin, 1984).…”
Section: Introductionmentioning
confidence: 99%